Grazing by the calanoid copepod Neocalanus cristatus on the microbial food web in the coastal Gulf of Alaska - Liu, Hongbin; Dagg, Michael J.; Strom, Suzanne (Journal of Plankton Research, 2005)
Neocalanus cristatus feeding on phytoplankton and microzooplankton was measured in the coastal Gulf of Alaska during spring and early summer of 2001 and 2003. Neocalanus cristatus CV fed primarily on particles >20 μm. Particles in the 5- to 20-μm size range were ingested in some experiments under nonbloom conditions but not under bloom conditions. Particles <5 μm were not ingested but increased during incubations because N. cristatus consumed their microzooplanktonic predators. Neocalanus cristatus are sufficiently abundant in nature to induce such a cascade effect in situ . Microzooplankton provided >70% of the carbon ingested by N. cristatus under nonbloom conditions but only ∼30% under bloom conditions. Neocalanus cristatus ingested about two times more carbon under bloom conditions (average 21.4 μg C copepod−1 day−1) than under nonbloom conditions (average 10.0 μg C copepod−1 day−1), but these rates were inadequate to meet nutritional demands for growth and metabolism, estimated to be between 40 and 140 μg C copepod−1 day−1. We believe our ingestion rates are underestimates of in situ rates because (i) we are underestimating consumption rates of large particles, (ii) we may not be including some very large particles that should be considered as diet items and (iii) we are not properly accounting for the ingestion of aggregates. The feeding behavior of N. cristatus , one of the most abundant copepods in the North Pacific Ocean, remains incompletely understood.